Analysis of the Potential Development of Ecological Cocoa Agrotourism to Increase Farmers' Income in Tumbudadio Village Tirawuta Sub-district, East Kolaka Regency - Rahmayani, Rahmayani; Weka Gusmiarty Abdullah; Samsul Alam Fyka (International Journal of Technology and Education Research, 2024)
This study aims to describe the description of farmers' income source activities before and after the development of ecological cocoa agrotourism and analyze the potential of the concept of Attractions, Amenities, and Accessibility (3A) in the development of ecological cocoa agrotourism to increase farmers' income in Tumbudadio Village, Tirawuta District, East Kolaka Regency. The population in this study is farmers who are included in the ecological cocoa agrotourism development area, which is four people; the surrounding community is four people; the Village Head is one person; and the Tirawuta Sub-district is one person. This study uses census sampling techniques for the farmer population and purposive sampling for the surrounding community population, village heads, and sub-district heads. The variables in this study are farmers' income, production costs, number of agricultural products, selling prices, receipts, attractions, amenities, and accessibility. The analysis used is income analysis, income difference test analysis, and potential analysis of Attractions, Amenities, and Accessibility (3A). The results of the study show that the source of income of farmers before the existence of cocoa agrotourism from cocoa, patchouli, paddy rice, and pepper farming, with an average profit of IDR 3,397,464 per month, while after the existence of ecological cocoa agrotourism from farming activities plus tourism activities in the ecological cocoa agrotourism area, with an average profit of IDR 12,630,000 per month. The development of ecological cocoa agrotourism has high potential because the source of income for respondent farmers through ecological cocoa agrotourism has a positive impact on increasing farmers' income. Regarding attractions, ecological cocoa agrotourism offers learning activities on cocoa cultivation, the process of making cocoa products into chocolate, and natural tourism with beautiful scenery. Appeasurable facilities include toilets, dining areas, and eco-friendly accommodations for tourists. Accessibility consists of the ease of reaching agro-tourism locations with various modes of transportation and the presence of clear directions